Micah - Zapff, Burkard M. (Kohlhammer Verlag, 2022)
Major parts of the book of Micah were probably composed in the context of a book containing a number of prophetic writings - even as many as twelve. They can therefore only be understood and interpreted adequately within that context. That process of interpretation sheds light on an essential segment of the history of Old Testament theology: it was not primarily a matter of the statements of lone individual prophetic figures but of a common testimony to YHWH's speaking and acting in the history of his people. Zapff shows this by reflecting diachronically on the results of his synchronic exegesis and so tracing the process by which the Micah document and its theological statement were formed. --Back cover